CN117584569A - Fire resistant laminate - Google Patents
Fire resistant laminate Download PDFInfo
- Publication number
- CN117584569A CN117584569A CN202310369715.3A CN202310369715A CN117584569A CN 117584569 A CN117584569 A CN 117584569A CN 202310369715 A CN202310369715 A CN 202310369715A CN 117584569 A CN117584569 A CN 117584569A
- Authority
- CN
- China
- Prior art keywords
- fire
- laminate
- layer
- flame
- acrylate
- Prior art date
- Legal status (The legal status is an assumption and is not a legal conclusion. Google has not performed a legal analysis and makes no representation as to the accuracy of the status listed.)
- Pending
Links
Classifications
-
- B—PERFORMING OPERATIONS; TRANSPORTING
- B32—LAYERED PRODUCTS
- B32B—LAYERED PRODUCTS, i.e. PRODUCTS BUILT-UP OF STRATA OF FLAT OR NON-FLAT, e.g. CELLULAR OR HONEYCOMB, FORM
- B32B25/00—Layered products comprising a layer of natural or synthetic rubber
- B32B25/20—Layered products comprising a layer of natural or synthetic rubber comprising silicone rubber
-
- B—PERFORMING OPERATIONS; TRANSPORTING
- B32—LAYERED PRODUCTS
- B32B—LAYERED PRODUCTS, i.e. PRODUCTS BUILT-UP OF STRATA OF FLAT OR NON-FLAT, e.g. CELLULAR OR HONEYCOMB, FORM
- B32B27/00—Layered products comprising a layer of synthetic resin
- B32B27/30—Layered products comprising a layer of synthetic resin comprising vinyl (co)polymers; comprising acrylic (co)polymers
- B32B27/308—Layered products comprising a layer of synthetic resin comprising vinyl (co)polymers; comprising acrylic (co)polymers comprising acrylic (co)polymers
-
- B—PERFORMING OPERATIONS; TRANSPORTING
- B32—LAYERED PRODUCTS
- B32B—LAYERED PRODUCTS, i.e. PRODUCTS BUILT-UP OF STRATA OF FLAT OR NON-FLAT, e.g. CELLULAR OR HONEYCOMB, FORM
- B32B25/00—Layered products comprising a layer of natural or synthetic rubber
- B32B25/02—Layered products comprising a layer of natural or synthetic rubber with fibres or particles being present as additives in the layer
-
- B—PERFORMING OPERATIONS; TRANSPORTING
- B32—LAYERED PRODUCTS
- B32B—LAYERED PRODUCTS, i.e. PRODUCTS BUILT-UP OF STRATA OF FLAT OR NON-FLAT, e.g. CELLULAR OR HONEYCOMB, FORM
- B32B25/00—Layered products comprising a layer of natural or synthetic rubber
- B32B25/10—Layered products comprising a layer of natural or synthetic rubber next to a fibrous or filamentary layer
-
- B—PERFORMING OPERATIONS; TRANSPORTING
- B32—LAYERED PRODUCTS
- B32B—LAYERED PRODUCTS, i.e. PRODUCTS BUILT-UP OF STRATA OF FLAT OR NON-FLAT, e.g. CELLULAR OR HONEYCOMB, FORM
- B32B27/00—Layered products comprising a layer of synthetic resin
- B32B27/12—Layered products comprising a layer of synthetic resin next to a fibrous or filamentary layer
-
- B—PERFORMING OPERATIONS; TRANSPORTING
- B32—LAYERED PRODUCTS
- B32B—LAYERED PRODUCTS, i.e. PRODUCTS BUILT-UP OF STRATA OF FLAT OR NON-FLAT, e.g. CELLULAR OR HONEYCOMB, FORM
- B32B27/00—Layered products comprising a layer of synthetic resin
- B32B27/18—Layered products comprising a layer of synthetic resin characterised by the use of special additives
-
- B—PERFORMING OPERATIONS; TRANSPORTING
- B32—LAYERED PRODUCTS
- B32B—LAYERED PRODUCTS, i.e. PRODUCTS BUILT-UP OF STRATA OF FLAT OR NON-FLAT, e.g. CELLULAR OR HONEYCOMB, FORM
- B32B5/00—Layered products characterised by the non- homogeneity or physical structure, i.e. comprising a fibrous, filamentary, particulate or foam layer; Layered products characterised by having a layer differing constitutionally or physically in different parts
- B32B5/02—Layered products characterised by the non- homogeneity or physical structure, i.e. comprising a fibrous, filamentary, particulate or foam layer; Layered products characterised by having a layer differing constitutionally or physically in different parts characterised by structural features of a fibrous or filamentary layer
- B32B5/022—Non-woven fabric
-
- B—PERFORMING OPERATIONS; TRANSPORTING
- B32—LAYERED PRODUCTS
- B32B—LAYERED PRODUCTS, i.e. PRODUCTS BUILT-UP OF STRATA OF FLAT OR NON-FLAT, e.g. CELLULAR OR HONEYCOMB, FORM
- B32B5/00—Layered products characterised by the non- homogeneity or physical structure, i.e. comprising a fibrous, filamentary, particulate or foam layer; Layered products characterised by having a layer differing constitutionally or physically in different parts
- B32B5/02—Layered products characterised by the non- homogeneity or physical structure, i.e. comprising a fibrous, filamentary, particulate or foam layer; Layered products characterised by having a layer differing constitutionally or physically in different parts characterised by structural features of a fibrous or filamentary layer
- B32B5/024—Woven fabric
-
- B—PERFORMING OPERATIONS; TRANSPORTING
- B32—LAYERED PRODUCTS
- B32B—LAYERED PRODUCTS, i.e. PRODUCTS BUILT-UP OF STRATA OF FLAT OR NON-FLAT, e.g. CELLULAR OR HONEYCOMB, FORM
- B32B5/00—Layered products characterised by the non- homogeneity or physical structure, i.e. comprising a fibrous, filamentary, particulate or foam layer; Layered products characterised by having a layer differing constitutionally or physically in different parts
- B32B5/02—Layered products characterised by the non- homogeneity or physical structure, i.e. comprising a fibrous, filamentary, particulate or foam layer; Layered products characterised by having a layer differing constitutionally or physically in different parts characterised by structural features of a fibrous or filamentary layer
- B32B5/026—Knitted fabric
-
- B—PERFORMING OPERATIONS; TRANSPORTING
- B32—LAYERED PRODUCTS
- B32B—LAYERED PRODUCTS, i.e. PRODUCTS BUILT-UP OF STRATA OF FLAT OR NON-FLAT, e.g. CELLULAR OR HONEYCOMB, FORM
- B32B5/00—Layered products characterised by the non- homogeneity or physical structure, i.e. comprising a fibrous, filamentary, particulate or foam layer; Layered products characterised by having a layer differing constitutionally or physically in different parts
- B32B5/02—Layered products characterised by the non- homogeneity or physical structure, i.e. comprising a fibrous, filamentary, particulate or foam layer; Layered products characterised by having a layer differing constitutionally or physically in different parts characterised by structural features of a fibrous or filamentary layer
- B32B5/028—Net structure, e.g. spaced apart filaments bonded at the crossing points
-
- B—PERFORMING OPERATIONS; TRANSPORTING
- B32—LAYERED PRODUCTS
- B32B—LAYERED PRODUCTS, i.e. PRODUCTS BUILT-UP OF STRATA OF FLAT OR NON-FLAT, e.g. CELLULAR OR HONEYCOMB, FORM
- B32B7/00—Layered products characterised by the relation between layers; Layered products characterised by the relative orientation of features between layers, or by the relative values of a measurable parameter between layers, i.e. products comprising layers having different physical, chemical or physicochemical properties; Layered products characterised by the interconnection of layers
- B32B7/04—Interconnection of layers
- B32B7/12—Interconnection of layers using interposed adhesives or interposed materials with bonding properties
-
- H—ELECTRICITY
- H01—ELECTRIC ELEMENTS
- H01M—PROCESSES OR MEANS, e.g. BATTERIES, FOR THE DIRECT CONVERSION OF CHEMICAL ENERGY INTO ELECTRICAL ENERGY
- H01M10/00—Secondary cells; Manufacture thereof
- H01M10/05—Accumulators with non-aqueous electrolyte
- H01M10/052—Li-accumulators
-
- H—ELECTRICITY
- H01—ELECTRIC ELEMENTS
- H01M—PROCESSES OR MEANS, e.g. BATTERIES, FOR THE DIRECT CONVERSION OF CHEMICAL ENERGY INTO ELECTRICAL ENERGY
- H01M50/00—Constructional details or processes of manufacture of the non-active parts of electrochemical cells other than fuel cells, e.g. hybrid cells
- H01M50/10—Primary casings; Jackets or wrappings
- H01M50/14—Primary casings; Jackets or wrappings for protecting against damage caused by external factors
- H01M50/143—Fireproof; Explosion-proof
-
- H—ELECTRICITY
- H01—ELECTRIC ELEMENTS
- H01M—PROCESSES OR MEANS, e.g. BATTERIES, FOR THE DIRECT CONVERSION OF CHEMICAL ENERGY INTO ELECTRICAL ENERGY
- H01M50/00—Constructional details or processes of manufacture of the non-active parts of electrochemical cells other than fuel cells, e.g. hybrid cells
- H01M50/20—Mountings; Secondary casings or frames; Racks, modules or packs; Suspension devices; Shock absorbers; Transport or carrying devices; Holders
- H01M50/218—Mountings; Secondary casings or frames; Racks, modules or packs; Suspension devices; Shock absorbers; Transport or carrying devices; Holders characterised by the material
- H01M50/22—Mountings; Secondary casings or frames; Racks, modules or packs; Suspension devices; Shock absorbers; Transport or carrying devices; Holders characterised by the material of the casings or racks
- H01M50/231—Mountings; Secondary casings or frames; Racks, modules or packs; Suspension devices; Shock absorbers; Transport or carrying devices; Holders characterised by the material of the casings or racks having a layered structure
-
- H—ELECTRICITY
- H01—ELECTRIC ELEMENTS
- H01M—PROCESSES OR MEANS, e.g. BATTERIES, FOR THE DIRECT CONVERSION OF CHEMICAL ENERGY INTO ELECTRICAL ENERGY
- H01M50/00—Constructional details or processes of manufacture of the non-active parts of electrochemical cells other than fuel cells, e.g. hybrid cells
- H01M50/20—Mountings; Secondary casings or frames; Racks, modules or packs; Suspension devices; Shock absorbers; Transport or carrying devices; Holders
- H01M50/233—Mountings; Secondary casings or frames; Racks, modules or packs; Suspension devices; Shock absorbers; Transport or carrying devices; Holders characterised by physical properties of casings or racks, e.g. dimensions
- H01M50/24—Mountings; Secondary casings or frames; Racks, modules or packs; Suspension devices; Shock absorbers; Transport or carrying devices; Holders characterised by physical properties of casings or racks, e.g. dimensions adapted for protecting batteries from their environment, e.g. from corrosion
-
- H—ELECTRICITY
- H01—ELECTRIC ELEMENTS
- H01M—PROCESSES OR MEANS, e.g. BATTERIES, FOR THE DIRECT CONVERSION OF CHEMICAL ENERGY INTO ELECTRICAL ENERGY
- H01M50/00—Constructional details or processes of manufacture of the non-active parts of electrochemical cells other than fuel cells, e.g. hybrid cells
- H01M50/20—Mountings; Secondary casings or frames; Racks, modules or packs; Suspension devices; Shock absorbers; Transport or carrying devices; Holders
- H01M50/249—Mountings; Secondary casings or frames; Racks, modules or packs; Suspension devices; Shock absorbers; Transport or carrying devices; Holders specially adapted for aircraft or vehicles, e.g. cars or trains
-
- B—PERFORMING OPERATIONS; TRANSPORTING
- B32—LAYERED PRODUCTS
- B32B—LAYERED PRODUCTS, i.e. PRODUCTS BUILT-UP OF STRATA OF FLAT OR NON-FLAT, e.g. CELLULAR OR HONEYCOMB, FORM
- B32B2255/00—Coating on the layer surface
- B32B2255/02—Coating on the layer surface on fibrous or filamentary layer
-
- B—PERFORMING OPERATIONS; TRANSPORTING
- B32—LAYERED PRODUCTS
- B32B—LAYERED PRODUCTS, i.e. PRODUCTS BUILT-UP OF STRATA OF FLAT OR NON-FLAT, e.g. CELLULAR OR HONEYCOMB, FORM
- B32B2255/00—Coating on the layer surface
- B32B2255/26—Polymeric coating
-
- B—PERFORMING OPERATIONS; TRANSPORTING
- B32—LAYERED PRODUCTS
- B32B—LAYERED PRODUCTS, i.e. PRODUCTS BUILT-UP OF STRATA OF FLAT OR NON-FLAT, e.g. CELLULAR OR HONEYCOMB, FORM
- B32B2262/00—Composition or structural features of fibres which form a fibrous or filamentary layer or are present as additives
- B32B2262/10—Inorganic fibres
- B32B2262/101—Glass fibres
-
- B—PERFORMING OPERATIONS; TRANSPORTING
- B32—LAYERED PRODUCTS
- B32B—LAYERED PRODUCTS, i.e. PRODUCTS BUILT-UP OF STRATA OF FLAT OR NON-FLAT, e.g. CELLULAR OR HONEYCOMB, FORM
- B32B2264/00—Composition or properties of particles which form a particulate layer or are present as additives
- B32B2264/10—Inorganic particles
- B32B2264/102—Oxide or hydroxide
- B32B2264/1023—Alumina
-
- B—PERFORMING OPERATIONS; TRANSPORTING
- B32—LAYERED PRODUCTS
- B32B—LAYERED PRODUCTS, i.e. PRODUCTS BUILT-UP OF STRATA OF FLAT OR NON-FLAT, e.g. CELLULAR OR HONEYCOMB, FORM
- B32B2307/00—Properties of the layers or laminate
- B32B2307/30—Properties of the layers or laminate having particular thermal properties
- B32B2307/306—Resistant to heat
- B32B2307/3065—Flame resistant or retardant, fire resistant or retardant
-
- B—PERFORMING OPERATIONS; TRANSPORTING
- B32—LAYERED PRODUCTS
- B32B—LAYERED PRODUCTS, i.e. PRODUCTS BUILT-UP OF STRATA OF FLAT OR NON-FLAT, e.g. CELLULAR OR HONEYCOMB, FORM
- B32B2307/00—Properties of the layers or laminate
- B32B2307/70—Other properties
- B32B2307/732—Dimensional properties
- B32B2307/737—Dimensions, e.g. volume or area
- B32B2307/7375—Linear, e.g. length, distance or width
- B32B2307/7376—Thickness
-
- H—ELECTRICITY
- H01—ELECTRIC ELEMENTS
- H01M—PROCESSES OR MEANS, e.g. BATTERIES, FOR THE DIRECT CONVERSION OF CHEMICAL ENERGY INTO ELECTRICAL ENERGY
- H01M2220/00—Batteries for particular applications
- H01M2220/20—Batteries in motive systems, e.g. vehicle, ship, plane
Landscapes
- Chemical & Material Sciences (AREA)
- Chemical Kinetics & Catalysis (AREA)
- Electrochemistry (AREA)
- General Chemical & Material Sciences (AREA)
- Engineering & Computer Science (AREA)
- Textile Engineering (AREA)
- Manufacturing & Machinery (AREA)
- Aviation & Aerospace Engineering (AREA)
- Laminated Bodies (AREA)
Abstract
防火层压材料(3),包括按规定顺序的以下层:‑由硅酸盐玻璃纤维组成的无机纤维层;‑阻燃硅酮橡胶层,和‑胶粘剂层,其中胶粘剂为包含至少一种选自氧化铝和氢氧化铝的阻燃剂组分的丙烯酸酯胶粘剂,所述防火层压材料具有非常好的防火性能,并且特别适用于保护蓄电池。
Fire-resistant laminate (3), comprising the following layers in the specified order: - an inorganic fiber layer consisting of silicate glass fibers; - a flame-retardant silicone rubber layer, and - an adhesive layer, wherein the adhesive is composed of at least one selected An acrylic adhesive with a flame retardant component of aluminum oxide and aluminum hydroxide, the fireproof laminate has very good fireproof properties and is particularly suitable for protecting batteries.
Description
Technical Field
The present invention relates to fire resistant laminates (fire resistant laminates) for protecting flammable objects, such as battery packs for electric vehicles, and the use of such fire resistant laminates.
Background
In the process of converting to more environmentally friendly energy, the importance of rechargeable batteries (also called secondary batteries or accumulators, akkus for short) is rapidly increasing. They are used not only in smaller appliances, but also in, for example, electric vehicles. In particular, lithium ion secondary batteries have been widely accepted as rechargeable batteries.
For all the advantages brought about by lithium ion batteries, the main problem is the possible mechanical damage to the battery, which can lead to internal electrical shorts and to battery heating. Overheating may also occur when an error occurs during charging. If the heating exceeds a certain limit and expands in the battery, so-called thermal runaway (english) occurs. The exothermic reaction occurring in the battery is further accelerated by the generated heat and releases more and more heat. In this case, the battery can be caused to fire, in particular when the heat generated is so great that the plastic surrounding the battery melts and ignites.
This is a considerable risk, in particular in the case of electrically driven vehicles, when a fire is thereby caused to the entire vehicle, in particular because the accumulator is located underneath the passenger compartment. If a fire occurs in the area of the battery, it is necessary to prevent or at least delay the spread of the fire to the passenger compartment and endanger the safety of the personnel in the vehicle.
According to annex 20 of global electric vehicle safety regulations (Global Technical Regulation on the Electric Vehicle Safety (EVS) ") which was issued in 2018, after thermal runaway, if the thermal runaway cannot be terminated, after a warning of thermal runaway, the battery system must withstand at least 5 minutes before the flame of the battery system can escape to the outside, the battery explodes or smoke enters the passenger compartment, in order for the occupant to have an opportunity and enough time to escape from the interior of the vehicle.
In the prior art, various solutions are found for this purpose. In addition to preventing thermal runaway by first avoiding the occurrence of short circuits as everything as possible, many solutions have been proposed, such as the possibility of packaging batteries or the provision of a housing to prevent flames.
The battery system is usually enclosed in a steel or aluminum housing. Because these alone generally do not meet the above requirements, the prior art describes a number of thermal protection and barrier elements that can prevent fires/explosions for a sufficiently long period of time.
The use of glass fiber materials is particularly important here. For example, US 2005/0170238 A1 describes a battery housing made of a glass fiber reinforced polymer. Furthermore, WO 2014/053623 describes a battery housing having a flexible casing made of an endothermic reactive heat absorbing material and a hose-like exhaust pipe with a sheath made of a high temperature resistant textile.
Many laminates that have been proposed as fire protection also include one or more forms of fiberglass or fiberglass fabric.
Known from CN 207028393U is a laminate consisting of a fabric layer, in particular formed of a glass fabric, nylon or polyester fabric, a silicone-ceramic-silicone rubber layer and an adhesive layer.
WO 2021/144758 A1 describes a multilayer heat insulation device having a core layer comprising a plurality of fibers (in particular glass fibers) or flame-retardant foam, and further layers applied to or integrated in the core layer, wherein the layers should have a low thermal conductivity and likewise consist of inorganic binders or inorganic fibers with inorganic fillers. Additional layers may also be provided, such as layers formed of silicone, acrylate, or polyurethane.
WO 2020/070275 A1 discloses a composite system consisting of: various minerals have been proposed in particular for this purpose, a carrier layer made of a glass fiber nonwoven or fabric, an adhesive layer made of a thermoplastic polymer elastomer, water glass, polyurethane or acrylate, and a flame-resistant layer made of a glass fiber nonwoven or fabric with an ablative coating. Furthermore, a stainless steel foil may be provided as an intermediate layer.
The problem is that the requirements for materials for preventing or delaying the effects of thermal runaway are very high. High voltage builds up in the cell until the unit cell eventually bursts. The temperatures generated are huge and can reach temperatures above 1000 ℃. Worse, in the case of vehicle batteries, the space available is often very limited and, depending on the design, fire-protection materials in many cases only allow for very low layer thicknesses. Thus, only 1-3mm of free space is typically provided into which the fire-protecting material may be inserted. While many materials with a thickness of 3mm still meet fire protection requirements, this is often not the case for materials with a thickness of less than 3mm or even 2mm and below.
Finally, it is not easy to apply fire resistant laminates precisely because conventional laminates are generally stiff (rigid) and laminates have a range of dimensions. Once fixed, the composite systems known in the art can often no longer be removed to correct for incorrect positioning. Furthermore, many known laminates are very stiff and therefore not well applicable.
Disclosure of Invention
It is therefore an object of the present invention to provide a fire-resistant laminate which is able to meet the requirements of fire regulations, in particular regulations which require a period of time of 5 minutes from thermal runaway to explosion, open flame and/or smoke generation in the passenger compartment, and which has a total thickness of less than 3 mm. Furthermore, the fire resistant laminate should be easy to apply and, if possible, not immediately firmly secured to the substrate upon application so as to be no longer repositionable.
This object is solved by the fire resistant laminate according to the invention. Advantageous further developments of the subject matter of the invention are described below. Furthermore, the invention also includes the use of the laminate according to the invention.
The invention thus relates to a fire-resistant laminate of the kind mentioned at the outset, comprising the following layers in the stated order:
-an inorganic fiber layer consisting of silicate glass fibers;
-a flame retardant silicone rubber layer, and
-an adhesive layer, wherein the adhesive is an acrylate adhesive comprising at least one flame retardant component selected from the group consisting of alumina and aluminum hydroxide.
Such a fire-resistant laminate according to the invention has very good fire-resistant properties and makes it possible to avoid or at least delay open fires even at very low layer thicknesses of only 2mm or less. Various Test methods are used to check the fire resistance, in particular the so-called "burn Test" (english:, burn Test ") and the" battery impact Test "(english:, battery Impact Test").
Drawings
Fig. 1 shows a test apparatus for a combustion test.
Fig. 2 shows a test device for battery impact test.
Detailed Description
The test apparatus (or test assembly) for the combustion test is shown in fig. 1. The laminate to be tested was placed between a 0.7mm thick steel plate with a cathodic dip (KTL) coating, which simulates the casing of a vehicle battery, and a butane gas flame at a temperature of 1200 ℃. A hot flame at 1200℃was applied to the test apparatus for 10 minutes. During this time, the temperature of the "cold side", which is a measurement away from the flame, should not exceed 300 ℃.
The battery impact test simulates a short-circuit phase of the battery, in which not only a fire occurs, but also hot particles are released due to the very high temperature. This scene is simulated by means of pyrotechnics. Within 22 seconds, a 22mm caliber pyrotechnic is bombarded at a distance of 20mm onto a 2mm thick aluminum plate onto which the laminate to be tested is applied. The test apparatus is shown in fig. 2. If the pyrotechnic fire did not burn through the aluminum plate during the 22 second bombardment, the test was passed.
These two test methods are described in detail in connection with the examples. Other test methods relevant in the testing of the fire safety performance of batteries are likewise presented there.
In a particularly advantageous embodiment of the invention, the silicate glass fibers of the fire-resistant laminate have a silica content of at least 94%, in particular at least 96%. Such fibers have particularly high temperature stability. Depending on the weave structure, these fibers can withstand temperatures up to about 1,100 to 1,200 ℃.
The inorganic fiber layer may be designed in the form of drawn (loop) knits, laid scrims (lay scrims), webbing, knits, needle-pile textiles, felts, fabrics (including plain, twill and satin weaves), looped knits (including warp knit fabrics and knitted apparel fabrics) or nonwovens, wherein "nonwoven" is understood to mean at least textile sheet structures according to EN 29092 (1988) as well as stitch-bonded nonwovens and similar systems. In addition, a spacer loop knitted fabric and a spacer fabric formed by lamination can also be used. A spacer fabric of this type is disclosed in EP 0 071212 B1. The spacer fabric is a mat-like layered body having a top layer formed of a fibrous or silk nonwoven, a bottom layer, and individual or bundled anchoring fibers present between the layers, which anchoring fibers are needled in a distributed fashion across the area of the layered body through the particulate layer and connect the top and bottom layers to one another.
Particularly preferably, the inorganic fiber layer composed of silicate glass fibers is a satin weave, in particular of the 12H, 8H or 8/3 type. The warp threads preferably have a length of 16 to 20cm -1 The weft has a thread count of 12 to 16cm -1 Is a line number of (a) in a line number of (b). Very particular preference is given to using 8H satin fabrics having a length of 19cm -1 Is 14cm -1 Is a number of weft threads. Such fabrics are particularly temperature stable and resistant to mechanical stresses caused by hot particles.
It is particularly preferred that the flame retardant silicone rubber layer consists of a silicone rubber containing at least one type of particles selected from the group consisting of iron (III) oxide, ammonium polyphosphate, zinc borate and aluminum hydroxide. The mentioned particles can increase the temperature stability of the silicone rubber and thereby improve the fire resistance of the laminate.
There are a number of possibilities for the application of the silicone rubber layer. Advantageously, the flame retardant silicone rubber layer is applied to the inorganic fiber layer in a liquid calendaring process. In this way, a uniform application (or coating) is ensured, which is particularly important in the case of low layer thicknesses. Application of too thin in individual areas would jeopardize the overall protection. On the other hand, too thick an application results in the layer not being placed in the available space. The liquid calendering process ensures that the silicone rubber penetrates into the fabric to some extent and thus a stronger connection and compaction of the compound occurs, which improves the fire resistance.
As flame retardant components in the adhesive layer, numerous compounds can be considered, such as particles selected from the group consisting of iron (III) oxide, ammonium polyphosphate, zinc borate and aluminum hydroxide, which are also mentioned for the silicone rubber layer. In addition, there is also boron nitride. However, it is particularly preferred that the flame retardant component in the adhesive layer is selected from the group consisting of α -Al 2 O 3 、γ-Al 2 O 3 、α-Al(OH) 3 、γ-Al(OH) 3 At least one compound of alpha-AlO (OH) or gamma-AlO (OH), wherein alpha-Al 2 O 3 And alpha-Al (OH) 3 Are very particularly preferred because of their very strong cooling effect. These compounds react while forming water vapor which seeks to leave the adhesive outwardly. The water vapor formed is deposited between the laminate and the surface to which it is mounted (e.g., the housing surrounding the battery). A buffer layer of poor thermal conductivity is created which results in less heating of the opposite side of the surface.
Particularly preferably, the acrylate adhesive is a pressure sensitive adhesive. As a general term, a pressure-sensitive adhesive or pressure-sensitive adhesive substance according to the invention is understood to mean a substance which is permanently (or permanently) adhesive and adhesive at least at room temperature. The pressure-sensitive adhesive is characterized in that it can be applied to a substrate by pressure and remain adhered thereto without the need to specifically define the pressure to be applied and the duration of action of the pressure. Generally, but essentially depending on the exact nature of the pressure sensitive adhesive, the temperature and air humidity, and the substrate, a short minimum pressure effect that does not exceed a mild contact for a short period of time is sufficient to achieve the adhesive effect, in other cases a longer application time of higher pressure may be necessary.
Pressure sensitive adhesives have characteristic viscoelastic properties that result in durable tackiness and cohesiveness. They are characterized by both viscous flow processes and the formation of elastic restoring forces when they are mechanically deformed. The two processes have a specific ratio to each other in terms of their respective proportions, both depending on the exact composition, structure and degree of crosslinking of the pressure-sensitive adhesive, and also on the rate and duration of deformation, and on the temperature.
Proportional (or proportional) viscous flow is necessary for achieving adhesion. The viscous component (component) which is usually only generated by macromolecules having relatively high mobility enables good wetting of the substrates to be bonded and good flow onto the substrates to be bonded. A high viscous flow ratio leads to high pressure-sensitive adhesives (also referred to as tackiness or surface tackiness) and therefore often also to high adhesion. Highly crosslinked systems, crystalline polymers or glassy, cured polymers are generally not pressure-sensitive or at least only very little pressure-sensitive due to the lack of a flowable component.
Proportional (or proportional) elastic restoring force is necessary for cohesive realization. They are produced, for example, from very long-chain and high-crimp macromolecules and from physically or chemically crosslinked macromolecules and enable the transmission of forces acting on the adhesive bond. They result in that the adhesive bond can withstand the sustained load (e.g. in the form of a sustained shear load) acting thereon to a sufficient extent over a long period of time.
"Poly (meth) acrylate" is understood to mean a polymer obtainable by free-radical polymerization of acrylic and/or methacrylic monomers and optionally further copolymerizable monomers. More particularly, "poly (meth) acrylate" is understood to mean a polymer whose monomer base consists of acrylic acid, methacrylic acid, acrylic acid esters and/or methacrylic acid esters to an extent of at least 50% by weight, wherein the acrylic acid esters and/or methacrylic acid esters are present at least partially, preferably to an extent of at least 30% by weight, based on the total monomer base of the polymer concerned.
Preferably, the pressure-sensitive adhesive comprises a total of from 30 to 60% by weight, more preferably a total of from 35 to 45% by weight, of poly (meth) acrylate, based in each case on the total weight of the pressure-sensitive adhesive. One (single) poly (meth) acrylate or more poly (meth) acrylates may be present. When reference is made above and below to "poly (meth) acrylate", this shall always include the presence of a plurality of poly (meth) acrylates; also, when referring to "poly (meth) acrylate" or "all (total amount) of all poly (meth) acrylates" it is also intended to include the presence of only one single poly (meth) acrylate.
The glass transition temperature of the poly (meth) acrylate of the pressure sensitive adhesive according to the present invention is preferably <0 ℃, more preferably between-25 and-70 ℃. The glass transition temperature of the polymer or polymer blocks in the block copolymers is determined according to the invention by means of Dynamic Scanning Calorimetry (DSC). For this, about 5mg of untreated polymer sample was weighed into an aluminum crucible (volume 25. Mu.L) and closed with a cap. For the measurement, DSC 204F1 from Netzsch corporation was used. Operating under nitrogen for inertization. The sample was first cooled to-150 ℃, then heated to +150 ℃ at a rate of 10K/min, and cooled again to-150 ℃. The second heating profile which follows is again run at a speed of 10K/min and the change in heat capacity is recorded. The glass transition is considered as a step in the thermogram.
The poly (meth) acrylate of the pressure sensitive adhesive may preferably consist of the following monomers: n-butyl acrylate, n-butyl methacrylate, n-pentyl acrylate, n-pentyl methacrylate, n-pentyl acrylate, n-hexyl methacrylate, n-heptyl acrylate, n-octyl methacrylate, n-nonyl acrylate, isobutyl acrylate, isooctyl methacrylate, 2-ethylhexyl acrylate, 2-ethylhexyl methacrylate, 2-propylheptyl acrylate and 2-propylheptyl methacrylate, acrylic acid, methacrylic acid, itaconic acid, maleic acid, fumaric acid, crotonic acid, aconitic acid, dimethacrylate, β -acryloxypropionic acid, trichloroacrylic acid, vinyl acetic acid, vinyl phosphonic acid, maleic anhydride, hydroxyethyl acrylate, in particular 2-hydroxyethyl acrylate hydroxy propyl acrylate, in particular 3-hydroxy propyl acrylate, hydroxy butyl acrylate, in particular 4-hydroxy butyl acrylate, hydroxy hexyl acrylate, in particular 6-hydroxy hexyl acrylate, hydroxy ethyl methacrylate, in particular 2-hydroxy ethyl methacrylate, hydroxy propyl methacrylate, in particular 3-hydroxy propyl methacrylate, hydroxy butyl methacrylate, in particular 4-hydroxy butyl methacrylate, hydroxy hexyl methacrylate, in particular 6-hydroxy hexyl methacrylate, allyl alcohol, glycidyl acrylate, glycidyl methacrylate, methyl acrylate, ethyl acrylate, propyl acrylate, methyl methacrylate, ethyl methacrylate, benzyl acrylate, benzyl methacrylate, sec-butyl acrylate, tert-butyl acrylate, phenyl methacrylate, 4-acryloylmorpholine, isobornyl acrylate, isobornyl methacrylate, tert-butylphenyl acrylate, tert-butylphenyl methacrylate, dodecyl methacrylate, isodecyl acrylate, lauryl acrylate, n-undecyl acrylate, stearyl acrylate, tridecyl acrylate, behenyl acrylate, cyclohexyl methacrylate, cyclopentyl methacrylate, phenoxyethyl acrylate, phenoxyethyl methacrylate, 2-butoxyethyl acrylate, 3, 5-trimethylcyclohexyl acrylate, 3, 5-dimethyladamantanyl acrylate, 4-cumylphenyl methacrylate, cyanoethyl acrylate cyanoethyl methacrylate, 4-biphenyl acrylate, 4-biphenyl methacrylate, 2-naphthyl acrylate, 2-naphthyl methacrylate, tetrahydrofurfuryl acrylate, diethylaminoethyl methacrylate, dimethylaminoethyl acrylate, dimethylaminoethyl methacrylate, 3-methoxymethyl acrylate, 3-methoxybutyl acrylate, 2-phenoxyethyl methacrylate, butyldiglycol methacrylate, ethylene glycol acrylate, ethylene glycol monomethacrylate, methoxypolyethylene glycol methacrylate 350, methoxypolyethylene glycol methacrylate 500, propylene glycol monomethacrylate, butoxydiglycol methacrylate, ethoxytriglycol methacrylate, octafluoropentane acrylate, 2, 3-pentafluoropropyl methacrylate 2,3, 4-hexafluorobutyl methacrylate 2, 3-pentafluoropropyl methacrylate, 2,3, 4-hexafluorobutyl methacrylate 2,3, 4-heptafluorobutyl acrylate, 2,3, 4-heptafluorobutyl methacrylate 2,2,3,3,4,4,5,5,6,6,7,7,8,8,8-pentadecafluorooctyl methacrylate, dimethylaminopropyl acrylamide, dimethylaminopropyl methacrylamide, N- (1-methylundecyl) acrylamide, N- (N-butoxymethyl) acrylamide, N- (butoxymethyl) methacrylamide, N- (ethoxymethyl) acrylamide, N- (N-octadecyl) acrylamide; n, N-dialkyl substituted amides such as N, N-dimethylacrylamide and N, N-dimethylacrylamide; n-benzyl acrylamide, N-isopropyl acrylamide, N-tert-butyl acrylamide, N-tert-octyl acrylamide, N-methylolacrylamide, N-methylolmethacrylamide, acrylonitrile, methacrylonitrile; vinyl ethers such as vinyl methyl ether, ethyl vinyl ether, vinyl isobutyl ether; vinyl esters such as vinyl acetate; vinyl halides, vinylidene halides, vinyl pyridine, 4-vinyl pyridine, N-vinyl phthalimide, N-vinyl lactam, N-vinyl pyrrolidone, styrene, a-methyl and p-methyl styrene, alpha-butyl styrene, 4-N-decyl styrene, 3, 4-dimethoxy styrene.
The adhesive may be chemically crosslinked according to the prior art. This can be achieved by various mechanisms, such as electron beam curing, UV crosslinking, thermal crosslinking. In particular, UV crosslinking is used using commercially available photoinitiators, such as benzoin acrylates or phenyl ketones.
The polymerization of the (meth) acrylate monomers is preferably carried out exclusively in a UV-initiated manner to a certain degree of polymerization, wherein a mixture of polymer and monomer is present. This, typically pasty, mixture is then compounded with further components of the pressure-sensitive adhesive and further polymerized or crosslinked by UV irradiation only after the material has been shaped into a web. Thus, in the compounding of the pressure-sensitive adhesive, not the final (fully polymerized) polymer is used here, but rather a mixture of polymer and monomer is used, wherein the monomer also acts as solvent for the polymer.
Particularly preferably, the acrylate adhesive is an acrylate pressure sensitive adhesive produced by UV-initiated polymerization of substances. Such adhesives are particularly easy to handle and apply.
Further preferably, the acrylate adhesive is a pressure sensitive adhesive comprising:
a. at least one poly (meth) acrylate; and
b. at least 40 wt% of a flame retardant component in the adhesive layer, based on the total weight of the pressure sensitive adhesive, wherein the flame retardant component may be a single filler or a mixture of at least two fillers, wherein the mixture of at least two fillers comprises at least one filler Fi consisting of substantially slightly rounded particles sph 。
By "slightly rounded" is meant herein that the particles do not have corners and edges.
Preferred pressure sensitive adhesives comprise preferably at least 50% by weight, more preferably at least 55% by weight, of a flame retardant component, based in each case on the total weight of the pressure sensitive adhesive.
When the preferred pressure sensitive adhesive comprises at least 50% by weight of a mixture of at least two fillers (wherein the mixture comprises at least one filler Fi consisting of substantially slightly rounded particles) sph ) It has been shown, in this case, that filler mixtures of this type are able to produce certain properties of the adhesive tape, i.e. counteract the anisotropy, largely direction-independent.
The filler mixture preferably produces thermal conductivity of the pressure-sensitive adhesive which is weak or not anisotropic at all. The filler mixture thus preferably comprises at least one thermally conductive filler. In particular, the filler, which consists of particles that are at least substantially slightly rounded, is a thermally conductive filler.
The preferred slightly rounded filler also has a low electrical conductivity so that the filler in question exhibits, in addition to the thermal conductivity, the property of an electrical insulator or of imparting to the pressure-sensitive adhesive the property of an electrical insulator.
Electrical insulation properties are also desirable for the additional filler of the filler mixture of the preferred pressure sensitive adhesive. In particular, all fillers of the pressure-sensitive adhesive are electrically insulating. The pressure-sensitive adhesive is particularly preferably electrically insulating.
The electrical insulator has a specific resistance according to TRGS 727 of 10 or more 8 Omega cm material.
Preferably, only filler Fi sph Consists of particles that are substantially slightly rounded and are present in a weight excess compared to the further filler or all the further filler.
Filler Fi sph In particular of aluminium hydroxide, or thus of aluminium hydroxide particles which are substantially slightly rounded.
Very particularly preferably, the mixture of at least two fillers consists of aluminium hydroxide and aluminium oxide, wherein the aluminium hydroxide is present in the form of essentially slightly rounded particles.
Depending on the field of application and the desired properties of the pressure-sensitive adhesive, it may comprise further components and/or additives, and in each case exactly alone or in combination with one or more further additives or components.
The pressure sensitive adhesive may comprise at least one tackifier, which may also be referred to as an adhesive strength enhancer or an adhesive resin. According to the general understanding of the skilled person, "tackifier" is understood to mean the following oligomeric or polymeric resins: it increases the self-adhesion (tack, intrinsic adhesion) of the pressure-sensitive adhesive layer compared to an otherwise identical pressure-sensitive adhesive without tackifier.
In one embodiment, the pressure sensitive adhesive may comprise a dye, in particular a pigment and/or soot.
Preferably, the inorganic fiber layer is pre-treated prior to application of the flame retardant silicone rubber layer, wherein the pre-treatment is corona treatment, plasma treatment or application of a primer. This pretreatment ensures a particularly good connection between the inorganic fiber layer and the flame-retardant silicone rubber layer, which is very important in the laminate according to the invention, since the layers must remain connected to one another even under very high heat exposure.
In a further advantageous embodiment, the flame-retardant silicone rubber layer is pre-treated prior to the application of the adhesive layer, wherein the pre-treatment is corona treatment, plasma treatment or application of a primer. Corona treatment is preferably used. The pretreatment also ensures a particularly good connection and is precisely between the flame-retardant silicone rubber layer and the adhesive layer. The above applies with respect to the importance of a good connection of layers.
The laminate may have any thickness. However, it is characterized by the following great advantages: provides very good fire protection even at very small total thicknesses. Advantageously, the entire laminate has a thickness of 0.5 to 2.5mm, preferably 0.5 to 2mm and particularly preferably 0.8 to 1.5 mm. The thickness of the inorganic fiber layer is preferably 0.2 to 1.3mm, particularly preferably 0.3 to 0.9mm, and very particularly preferably 0.3 to 0.7mm. The flame-retardant silicone rubber layer preferably has a thickness of 0.35 to 1.8mm, particularly preferably a thickness of 0.35 to 1.2mm and very particularly preferably a thickness of 0.35 to 0.9 mm. The thickness of the adhesive layer is preferably from 0.05 to 0.15mm, particularly preferably from 0.05 to 0.13mm, and very particularly preferably from 0.1 to 0.125mm.
In a particularly preferred embodiment, the laminate according to the invention comprises only three layers, namely an inorganic fiber layer, a flame retardant silicone rubber layer and an adhesive layer with a flame retardant component.
The mechanical properties of the inorganic fiber layer can be further improved by means of further (additional) coatings, especially in the event of a fire. Thus, in another advantageous embodiment, the silicone-based layer is applied on the side of the inorganic fiber layer remote (or facing away) from the flame retardant silicone rubber layer. Advantageously, the weight per unit area of the silicone-based layer is between 5 and 50g/m 2 Between them.
In addition, the adhesive layer is covered with a release liner.
The laminate according to the invention can be used anywhere for fire protection. The laminate is particularly suitable as a fire protection for batteries, and in particular lithium ion batteries in this case. Furthermore, the laminate is particularly suitable for use in batteries for electric vehicles.
When a short circuit occurs in a battery of this type, a very high pressure is initially built up in the unit cell until the unit cell bursts due to the overpressure valve. In a few seconds, in addition to a "normal flame", severe particle leakage comparable to pyrotechnical effects also occurs. Depending on the cell type, such particle bombardment typically lasts 15 to 25 seconds.
The battery or cell pack is typically mounted in a housing, which is typically made of aluminum or steel and has a KTL coating. Such a housing can withstand a particle bombardment of 4 to 5 seconds, after which it melts and the particle bombardment and flame escape to the outside. Preferably, the laminate according to the invention is applied on the inside of the housing, in particular glued under the cover of the housing. If the laminate is applied to the inside of the housing, the time that the housing can withstand such particle bombardment can be correspondingly prolonged. The duration of the extension of the bearing time depends on the thickness of the laminate or its layers. Thus, the laminate according to the invention having a layer thickness of 2mm can withstand particle bombardment in lithium ion batteries, which typically lasts 22 seconds, so that flame escape and thus fire spread can be prevented.
Thus, the laminate according to the invention achieves adequate fire protection despite a very low layer thickness. This is particularly advantageous because in the case of batteries for electric vehicles, the space available is very limited. The laminate should ideally be mounted on a cover facing the passenger compartment inside the outer shell. The space available is typically a maximum of 2mm, and sometimes even smaller (less than 1.5mm or even less than 1.3 mm).
Many conventional fire resistant laminates are very stiff, which makes positioning difficult. The laminate according to the invention is also particularly advantageous because it is flexible and thus easy to install. Furthermore, due to the use of pressure sensitive adhesives, the laminate according to the invention is repositionable, that is to say, even if it has not been successfully installed in the desired position initially, this is not critical, since it can be peeled off again and repositioned.
Examples
The following exemplary experiments are intended to explain the present invention in more detail without wishing to unnecessarily limit the present invention by selecting the examples given.
The testing method comprises the following steps:
combustion Test (Burning Test)
The test apparatus for the combustion test is shown in fig. 1. The laminate (3) to be tested (test piece size: 70x 150 mm) was placed between a 0.7mm thick KTL coated steel plate (1) (which simulates the housing of a vehicle battery) and a butane gas flame (2) at 1200 ℃. A hot flame at 1200℃was applied to the test apparatus for 10 minutes. During this time, the temperature on the side away from the flame (4), i.e., the "cold side", should not exceed 300 ℃. The temperatures of the cold side (4) and the "hot side" (5) are detected by a temperature sensor (6).
The fuel gas used was butane gas, the burner power was 1.85kW. Such a burner closely mimics the conditions observed when a lithium ion battery burns. The cold side of the temperature sensor is a type K thermocouple and the hot side is a type K or type B thermocouple.
Battery impact test (Battery Impact Test)
The battery impact test simulates the short-circuit phase of a battery, in which case, due to the very high temperature, not only a fire occurs, but also hot particles are released. The test apparatus is shown in fig. 2. This situation is simulated by means of a pyrotechnic (7). Within 22 seconds, a 22mm caliber pyrotechnic is bombarded at a distance of 20mm onto a 2mm thick aluminum plate (1) on which the laminate (3) to be tested is applied (test piece size: 150x 150 mm). The time (in seconds) that the laminate was subjected to bombardment before breakthrough (or penetration) was given as a result. If the pyrotechnic fire did not burn through the aluminum plate (1) during the 22 second bombardment, the test was passed. Aluminum is particularly suitable for this test because it melts from a temperature of 660 c and therefore the test results are clearly visible if smoke or fire through the panel.
Flame testing
The fire behavior of the test body after flame treatment was determined on the basis of UL 94V. Here, the burn and afterglow times and the specimen burn drops were evaluated, as well as whether any drops ignited a cotton indicator located below the specimen, and exactly in the vertical direction of the specimen. Samples of size 125 x 13 x 1.2 (mm) 3 were burned with a bunsen burner and exactly twice, 10 seconds each. The fire-resistant laminate according to the invention must meet the UL94V0 standard (extinguishing vertically clamped samples within 10 seconds without burning dripping of the plastic melt and an afterglow of at most 30 seconds).
Sample manufacture
Manufacture of laminates
For the production of the laminates according to the invention, standard transfer tapes tesa 58394 were used and combined with a composite material (POLOTSK-STEKLOVOLOKNO-600+Elastosil R501/75OH+2%COLOR PASTE FL RED IRON OXIDE RAL 3013) are laminated together. The materials used for the comparative examples are given in table 1.
In this way, a laminate with a layer thickness of 1.2mm was produced. These are all subjected to a combustion test and, if the result of the combustion test is promising, to a battery impact test.
The results are summarized in table 1 below:
TABLE 1
* Average of 5 singles
* Cold side temperature after 10 min, flame temperature 1200 ℃, sample size 70mm x 150mm, vertical measurement
* Time until breakthrough
Most of the comparative examples 2-11 have shown a lack of applicability in combustion tests because the temperature on the "cold side" is far in excess of 300 ℃. Only the laminate according to the invention according to example 1 (which has a glass-fibre fabric-insulation composite(POLOTSK-STEKLOVOLOKNO-600+Elastosil R501/75OH+2%COLOR PASTE FL RED IRON OXDE RAL 3013) and adhesive tesa 58394) are maintained at a temperature below 300℃for the required 10 minutes, i.e. 278℃on the "cold side" away from the burner. Only here is the laminate functional enough insulation to prevent the backside of the aluminum layer from being heated.
In the battery impact test, the laminate according to example 1 can only reach 15 seconds, but the required 22 seconds can be reached with a slightly thicker (2 mm instead of 1.2 mm) laminate with otherwise identical composition.
Claims (15)
Priority Applications (3)
| Application Number | Priority Date | Filing Date | Title |
|---|---|---|---|
| CN202310369715.3A CN117584569A (en) | 2023-04-07 | 2023-04-07 | Fire resistant laminate |
| EP24721863.9A EP4688433A1 (en) | 2023-04-07 | 2024-04-05 | Fire protection laminate |
| PCT/EP2024/059361 WO2024209071A1 (en) | 2023-04-07 | 2024-04-05 | Fire protection laminate |
Applications Claiming Priority (1)
| Application Number | Priority Date | Filing Date | Title |
|---|---|---|---|
| CN202310369715.3A CN117584569A (en) | 2023-04-07 | 2023-04-07 | Fire resistant laminate |
Publications (1)
| Publication Number | Publication Date |
|---|---|
| CN117584569A true CN117584569A (en) | 2024-02-23 |
Family
ID=89918898
Family Applications (1)
| Application Number | Title | Priority Date | Filing Date |
|---|---|---|---|
| CN202310369715.3A Pending CN117584569A (en) | 2023-04-07 | 2023-04-07 | Fire resistant laminate |
Country Status (3)
| Country | Link |
|---|---|
| EP (1) | EP4688433A1 (en) |
| CN (1) | CN117584569A (en) |
| WO (1) | WO2024209071A1 (en) |
Citations (9)
| Publication number | Priority date | Publication date | Assignee | Title |
|---|---|---|---|---|
| WO1991018842A1 (en) * | 1990-05-28 | 1991-12-12 | Helmut Hoedt | Shaped bodies, process and device for producing shaped bodies |
| JP2000248126A (en) * | 1998-12-28 | 2000-09-12 | Fujikura Ltd | Halogen-free flame-retardant resin composition and flame-retardant electric wires and cables |
| CN1532247A (en) * | 2003-03-18 | 2004-09-29 | �����ɷ� | Flame-retardant pressure sensitive adhesive, its preparing process and its use in producing pressure sensitive adhesive tape |
| DE202009007700U1 (en) * | 2009-05-19 | 2009-10-08 | Lohmann Gmbh & Co. Kg | Lamination tape for solar modules |
| US20140004342A1 (en) * | 2011-02-11 | 2014-01-02 | Nitto Denko Corporation | Flame-retardant thermally-conductive pressure-sensitive adhesive sheet |
| CN107216418A (en) * | 2017-07-10 | 2017-09-29 | 芜湖扬展新材料科技服务有限公司 | The preparation method of Polyacrylate Composites |
| WO2019146926A1 (en) * | 2018-01-29 | 2019-08-01 | 주식회사 엘지화학 | Rechargeable battery and insulation plate for rechargeable battery |
| DE102020205048A1 (en) * | 2020-04-21 | 2021-10-21 | Tesa Se | Polyacrylate and pressure sensitive adhesive based thereon |
| US20220025220A1 (en) * | 2020-07-23 | 2022-01-27 | Tesa Se | Stanzling insbesondere zum dauerhaften Verschließen von Löchern |
Family Cites Families (11)
| Publication number | Priority date | Publication date | Assignee | Title |
|---|---|---|---|---|
| IL66103A0 (en) | 1981-07-27 | 1982-09-30 | Tesch G H | Mat shaped composite body and its preparation |
| US4686135A (en) * | 1985-01-29 | 1987-08-11 | Hiraoka & Co., Ltd. | Composite sheet material |
| TW200535205A (en) * | 2003-11-13 | 2005-11-01 | Lg Chemical Ltd | Adhesives having advanced flame-retardant property |
| US20050170238A1 (en) | 2004-02-04 | 2005-08-04 | Abu-Isa Ismat A. | Fire shielding battery case |
| DE102012019676B4 (en) | 2012-10-05 | 2017-10-26 | Stöbich Technology Gmbh | Battery transport container, battery transport container and battery transport device |
| CN207028393U (en) | 2017-04-27 | 2018-02-23 | 深圳市中宇恒通电热科技有限公司 | A kind of safe thermal conductivity heat-insulating piece of novel battery |
| EP3861575A1 (en) | 2018-10-05 | 2021-08-11 | Cuylits Holding GmbH | Fire protection device with a composite system, composite system and battery pack with a fire protection device |
| DE102018009870B4 (en) * | 2018-12-19 | 2022-03-24 | Lohmann Gmbh & Co. Kg | Adhesive tape and method for producing the adhesive tape |
| WO2021144758A1 (en) | 2020-01-15 | 2021-07-22 | 3M Innovative Properties Company | Thermal runaway barrier for a rechargeable electrical energy storage system |
| DE102020007327A1 (en) * | 2020-12-01 | 2022-06-02 | H.K.O. Isolier- Und Textiltechnik Gmbh | Multilayer protection element for a battery |
| US20230018024A1 (en) * | 2021-07-19 | 2023-01-19 | Federal-Mogul Powertrain Llc | Thermal and dielectric insulator for battery pack |
-
2023
- 2023-04-07 CN CN202310369715.3A patent/CN117584569A/en active Pending
-
2024
- 2024-04-05 EP EP24721863.9A patent/EP4688433A1/en active Pending
- 2024-04-05 WO PCT/EP2024/059361 patent/WO2024209071A1/en not_active Ceased
Patent Citations (9)
| Publication number | Priority date | Publication date | Assignee | Title |
|---|---|---|---|---|
| WO1991018842A1 (en) * | 1990-05-28 | 1991-12-12 | Helmut Hoedt | Shaped bodies, process and device for producing shaped bodies |
| JP2000248126A (en) * | 1998-12-28 | 2000-09-12 | Fujikura Ltd | Halogen-free flame-retardant resin composition and flame-retardant electric wires and cables |
| CN1532247A (en) * | 2003-03-18 | 2004-09-29 | �����ɷ� | Flame-retardant pressure sensitive adhesive, its preparing process and its use in producing pressure sensitive adhesive tape |
| DE202009007700U1 (en) * | 2009-05-19 | 2009-10-08 | Lohmann Gmbh & Co. Kg | Lamination tape for solar modules |
| US20140004342A1 (en) * | 2011-02-11 | 2014-01-02 | Nitto Denko Corporation | Flame-retardant thermally-conductive pressure-sensitive adhesive sheet |
| CN107216418A (en) * | 2017-07-10 | 2017-09-29 | 芜湖扬展新材料科技服务有限公司 | The preparation method of Polyacrylate Composites |
| WO2019146926A1 (en) * | 2018-01-29 | 2019-08-01 | 주식회사 엘지화학 | Rechargeable battery and insulation plate for rechargeable battery |
| DE102020205048A1 (en) * | 2020-04-21 | 2021-10-21 | Tesa Se | Polyacrylate and pressure sensitive adhesive based thereon |
| US20220025220A1 (en) * | 2020-07-23 | 2022-01-27 | Tesa Se | Stanzling insbesondere zum dauerhaften Verschließen von Löchern |
Non-Patent Citations (1)
| Title |
|---|
| 刘建华编著: "建筑工业新材料", 30 June 2022, 中国建材工业出版社, pages: 124 - 127 * |
Also Published As
| Publication number | Publication date |
|---|---|
| EP4688433A1 (en) | 2026-02-11 |
| WO2024209071A1 (en) | 2024-10-10 |
Similar Documents
| Publication | Publication Date | Title |
|---|---|---|
| KR102486895B1 (en) | Thermal barrier materials for rechargeable electrical energy storage systems | |
| US20170301968A1 (en) | Thermal isolation material and methods of making and using the same | |
| US11845887B2 (en) | Diecut especially for permanently closing holes | |
| JPWO2019163839A1 (en) | Fireproof laminate and battery | |
| CN107406732B (en) | Decorative sheet and pressure-sensitive adhesive composition applied to decorative sheet | |
| KR102712509B1 (en) | Diecut especially for permanently closing holes | |
| WO2018181336A1 (en) | Double-sided adhesive tape | |
| JP6045929B2 (en) | Flame retardant thermal conductive adhesive sheet | |
| JP7529168B2 (en) | Secondary Battery Module | |
| WO2023149212A1 (en) | Secondary battery | |
| JP5533831B2 (en) | Flame retardant pressure sensitive adhesive and flame retardant pressure sensitive adhesive tape | |
| AU5998386A (en) | Crosslinked pressure-sensitive adhesive | |
| JP2017200998A (en) | Adhesive sheet | |
| CN114921203A (en) | Halogen-free flame-retardant pressure-sensitive adhesive and fireproof adhesive tape | |
| WO2025119978A1 (en) | Ceramizable composition with fire prevention and heat insulation, adhesive tape, preparation method and application | |
| EP4688433A1 (en) | Fire protection laminate | |
| JPH0525441A (en) | Pressure sensitive adhesive tape or sheet | |
| CN117769489B (en) | Die-cut parts specifically for permanently sealing holes | |
| WO2017191835A1 (en) | Adhesive sheet | |
| JP2022119663A (en) | Laminate, fireproof sheet, and battery | |
| JP2024091065A (en) | Heat-resistant sheet | |
| US20250002687A1 (en) | Pressure sensitive adhesive tape, article, and method of dismantling article | |
| WO2025119977A1 (en) | Ceramizable composition, adhesive film, adhesive tape, preparation method and application | |
| KR20250152165A (en) | Thermal runaway prevention Sheet using the same | |
| KR20250152166A (en) | Adhesive composition and thermal runaway prevention Sheet using the same |
Legal Events
| Date | Code | Title | Description |
|---|---|---|---|
| PB01 | Publication | ||
| PB01 | Publication | ||
| SE01 | Entry into force of request for substantive examination | ||
| SE01 | Entry into force of request for substantive examination |